2022
DOI: 10.3389/fpls.2022.1059559
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression profiling of PIN auxin efflux transporters reveal their role in developmental and abiotic stress conditions in rice

Abstract: The auxin efflux transporter proteins called PINs ferry auxin from its source to sinks in particular directions depending on their polar localizations in the plasma membrane, thus facilitating the development of the entire plant architecture. The rice genome has 12 PIN genes distributed over eight chromosomes. To study their roles in plant development, abiotic stress responsiveness, and shaping an auxin-dependent root architecture, a genome-wide analysis was carried out. Based on phylogeny, cellular localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 83 publications
(102 reference statements)
0
17
0
Order By: Relevance
“…Auxin is typically synthesized in axillary buds and leaf primordia and differentially distributed throughout the plant tissues by PIN family proteins that act as efflux carriers of auxin ( Sieberer and Leyser 2006 ; Swarup and Péret 2012 ). Depending on their polar localization, PINs ensure differential distribution of auxin that is vital for diverse developmental processes, including embryogenesis, tissue differentiation and organogenesis through upward, sideward, and downward transport ( Sieberer and Leyser 2006 ; Nguyen et al ., 2018 ; Manna et al ., 2022 ). In this study, the expression of PIN9 was found to be significantly up-regulated and the difference was 2.2-fold ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Auxin is typically synthesized in axillary buds and leaf primordia and differentially distributed throughout the plant tissues by PIN family proteins that act as efflux carriers of auxin ( Sieberer and Leyser 2006 ; Swarup and Péret 2012 ). Depending on their polar localization, PINs ensure differential distribution of auxin that is vital for diverse developmental processes, including embryogenesis, tissue differentiation and organogenesis through upward, sideward, and downward transport ( Sieberer and Leyser 2006 ; Nguyen et al ., 2018 ; Manna et al ., 2022 ). In this study, the expression of PIN9 was found to be significantly up-regulated and the difference was 2.2-fold ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that OsPIN9 functions in polar auxin transport and is involved in regulating adventitious root number and tiller number [55]. Recently, Manna et al (2022) [63] reported that salt and drought treatment significantly induced OsPIN9 expression, indicating the potential role of OsPIN9 in abiotic stress adaptation. In line with this, our previous study showed that mutation of OsPIN9 by CRISPR/Cas9 technology confers enhanced chilling tolerance in rice [64].…”
Section: Introductionmentioning
confidence: 97%
“…In addition to the PIN (PIN-FORMED) family, auxin transport is carried out by other types of proteins: AUX1/LAX (AUXIN-INSENSITIVE1/LIKE AUX1), ABCB (subfamily of ATP-binding cassette transporters), PILS (PIN-LIKES), NRT1.1 (nitrate transporter 1.1), and WAT1 (WALLS ARE THIN1) (Manna et al, 2022). It is believed that at a low pH of the apoplast, auxin becomes protonated and can penetrate into the cell by diffusion.…”
Section: Introductionmentioning
confidence: 99%